Positive Family Intervention for Children with ASD: Impact on Parents' Cognitions and Stress. - Mueller, Robert; Moskowitz, Lauren J. (Journal of Child & Family Studies, 2020)
While parent training often focuses on teaching parents of children with Autism Sepctrum Disorders (ASD) specific skills to address their child's problem behavior, it has often overlooked factors related to parents' own mental health and well-being, such as how they think and feel about their child's behavior and their parenting. The purpose of this study was to examine the impact of positive family intervention (PFI), a parent training program which combines cognitive-behavioral therapy (CBT) with family based positive behavior support (PBS), on parents' cognitions and children's problem behavior for families of children with ASD. A nonconcurrent multiple baseline design across three mothers was used to examine the impact of PFI on parent-reported stress, self-efficacy, attributions, rational and irrational beliefs, pessimism, and ratings of child behavior problems. Each mother received eight weekly 90-minute PFI sessions without the child present. Findings demonstrated significant decreases in parent ratings of problem behavior as well as observed child problem behavior for all three families, though visual analysis showed only modest change in parent-reported problem behavior for one of those three mothers, and direct observation data was only collected pre- and post-intervention. Two of the three mothers reported significant decreases in dysfunctional child- and parent-causal attributions, irrational beliefs, and pessimistic thoughts. In addition, one of those two mothers reported improvements in parental stress and self-efficacy. This study suggests that there may be benefits to incorporating CBT with PBS in terms of affecting parents' perceptions of their children and themselves. Factors potentially contributing to or limiting the effectiveness of PFI for each participant are discussed. Highlights: Child behavioral problems significantly decreased as a result of Positive Family Intervention (PFI). PFI resulted in improved cognitions or attitudes for two of the three mothers of children with ASD. Future research should identify which parents may benefit from adding parent–child coaching at home to parent-only sessions. Integrating cognitive-behavioral therapy with positive behavior support may help parents to implement behavioral interventions and cope with difficult situations.